Membrane and Soluble CD137 in Systemic Lupus Erythematosus: Role as Biomarkers for Disease Activity. (18th April 2023) - Ceccarelli, Fulvia; Natalucci, Francesco; Di Filippo, Alessandra; Olivieri, Giulio; Napoletano, Chiara; Rughetti, Aurelia; Nuti, Marianna; Zizzari, Ilaria Grazia; Conti, Fabrizio
Abstract : Objective . The role of T cells in the pathogenesis of systemic lupus erythematosus (SLE) has recently gained attention. Costimulatory molecules are membrane proteins strictly associated with T-cell receptor (TCR), acting by activating or inhibiting T cells and antigen-presenting cells (APC) through direct and reverse signaling, thus becoming responsible for the development of effector T cells or regulatory T cells. The primary objective of the present case–control study was to evaluate the cell membrane expression of CD137 on T cells and the serum concentration of CD137 (sCD137) in a SLE cohort. Materials . We enrolled SLE patients and sex/age-matched healthy subjects (HS). Disease activity was assessed by SLEDAI-2K. By application of flow cytometry, we evaluated the expression of CD137 on CD4+ and CD8+ lymphocytes. ELISA test was performed to evaluate serum levels of sCD137. Results . Twenty-one SLE patients (M/F 1/20; median age 48 years (IQR 17); median disease duration 144 months (IQR 204)) were evaluated. SLE patients showed %CD3+CD137+ cells significantly higher compared to HS (median 5.32 (IQR 6.11) versus 3.3 (IQR 1.8), p = 0.001 ). In SLE patients, %CD4+CD137+ cells positively correlated with SLEDAI-2K (p = 0.0082, r  = 0.58, CI (0.15–0.82); indeed, %CD4+CD137+ cells were significantly lower in SLE patients with a remission status compared to those not reaching this condition (median 1.07 (IQR 0.91) versus 1.58 (IQR 2.42), p = 0.013 ). Accordingly, sCD137 levels were significantly lower in remission status (31.30 pg/mL (IQR 102.2 versus median 122.8 pg/mL (IQR 536); p = 0.03 ) and correlated with %CD4+CD137+ cells (p = 0.012, r  = 0.60, CI (0.15–0.84)). Conclusion . Our results suggest a possible involvement of CD137-CD137L axis in SLE pathogenesis, as demonstrated by higher expression of CD137 on CD4+ cells in SLE compared with HS. Furthermore, the positive correlation between SLEDAI-2K and membrane CD137 expression on CD4+ cells, as well as soluble CD137, indicates a possible use as biomarkers for disease activity.